Cell-based and stem-cell-based treatments for spinal cord injury: evidence from clinical trials. Issue 7 (July 2022) - Zipser, Carl M; Cragg, Jacquelyn J; Guest, James D; Fehlings, Michael G; Jutzeler, Catherine R; Anderson, Aileen J; Curt, Armin
Summary: Spinal cord injury is a severely disabling neurological condition leading to impaired mobility, pain, and autonomic dysfunction. Most often, a single traumatic event, such as a traffic or recreational accident, leads to primary spinal cord damage through compression and laceration, followed by secondary damage consisting of inflammation and ischaemia, and culminating in substantial tissue loss. Patients need appropriate timely surgical and critical care, followed by neurorehabilitation to facilitate neuronal reorganisation and functional compensation. Although some neurological function might be regained, most patients with initially complete lesions have severe, irreversible neurological impairment. Cell-based and stem-cell-based therapies are recognised as promising candidates to promote functional recovery. However, no trials of these therapies in patients have yet provided reproducible evidence for clinical efficacy, challenged by small effect sizes, low immune suppression, and low sensitivity study designs. Nevertheless, in the past decade, clinical trials have shown the feasibility and long-term safety of cell transplantation into the injured spinal cord. This crucial milestone has paved the way to consider refinements and combined therapies, such as the use of biomaterials to augment the effects of cell transplantation. In the future, emerging cell types, scaffolding, and cell engineering might improve cell survival, integration, and therapeutic efficiency.